Against Sexual Violence in the Museum: Art, Curating, and Activism - Perry, Lara; Krasny, Elke (Journal of Cultural Analysis and Social Change, 2022)
Depictions of sexual violence are frequently found in the collections and displays of art museums, and material that represents and affirms violence against women often is displayed unchallenged. This article poses questions about how the presence of this material has been addressed in the relations between feminist activism against sexual violence, art made by artists responding to and participating in feminist activism, and the curatorial activities that have arisen to address the challenges that these activities present to art museums. The chapter investigates the 2021 exhibition Titian: Women, Myth and Power at the Isabella Stewart Gardner Museum and its handling of themes of rape in the central exhibit, Titian’s Rape of Europa; the history of themes of rape in feminist art since the 1970s and in exhibitions of this art that have taken place in museums in the last two decades; and curatorial engagements with sexual violence and rape in recent art exhibitions in the US and in the UK. The article argues that new strategies for the presentation and interpretation of artworks dealing with sexual violence are needed for museums to redress the patriarchal and colonial presence of sexual violence in their collection.
Keywords: Art Curating; Fine Arts; Museum; Museum Violence; Myriam; Rape; Sexual Violence; Visual activism

Accounting for Space, Place and Identity: GLBTIQ Young Adults’ Experiences and Understandings of Unwanted Sexual Attention in Clubs and Pubs - Fileborn, Bianca (Critical Criminology, 2014)
This article considers the role of space, place and identity in influencing gay, lesbian, bisexual, transgender/transsexual, intersex and queer (GLBTIQ) young adults’ experiences of unwanted sexual attention in licensed venues. It is argued in this article that the roles of space, place and identity are largely absent from theoretical understandings of sexual violence. Gender-based accounts of sexual violence, while important, are unable to fully account for sexual violence that is perpetrated within and against GLBTIQ communities. Drawing on data obtained through a mixed-methods study, in the first half of the article I establish the manner in which GLBTIQ young adults’ unique relationship with licensed venues appears to mediate the ways in which unwanted sexual attention occurring in these spaces is experienced and understood. The second half of this article is concerned with exploring the intersections between unwanted sexual attention and heterosexist violence and abuse in clubs and pubs. I conclude by considering the implications of these findings for theoretical understandings of sexual violence and unwanted sexual attention.
Keywords: Gender Identity; Intimate Partner Violence; Sexual Identity; Sexual Orientation; Sexual Violence